Synthesis, Characterization and Antimicrobial Activity of 3-Indolyl Chalcones - JAIN, SHRADDHA; CHOURASIA, O.P. (Asian Journal of Chemistry, 2010)
A series of new 3-indolyl chalcones have been prepared from the respective indole by treating with acetyl chloride in presence of ethanol to give 3-acetyl indol (I) then compound I react with aromatic aldehyde in presence of sodium hydroxide (2 %) in ethanol to give 3-indolyl chalcones.